Modelling the folding pathway of DNA nanostructures - Najafi, B (2022)
DNA origami is a robust technique for bottom-up nano-fabrication. It encodes a target shape into uniquely addressable interactions between a set of short 'staple' strands and a long 'scaffold' strand. The mechanisms of self-assembly, particularly regarding kinetics, need to be better understood. Origami design usually relies on optimising the thermodynamic stability of the target structure, and thermal annealing remains the most fool-proof assembly protocol. This work focuses on studying the folding pathway of three types of origami through simulations: a reconfigurable T-junction origami, several traditional origami, and origami with coated scaffolds.